Soil biodiversity promotes key ecosystem functions by its complex structure and interactions – state and perspectives - Liliane Ruess; Steffen Kolb; Nico Eisenhauer; Christian Ristok (Soil Organisms)
The biodiversity of soil microorganisms and fauna supports many ecosystem functions in terrestrial ecosystems, such as decomposition, aggregation of soil organic matter or mobilization and recycling of nutrients. These processes are linked to the functional traits (e.g. life strategy, body size, metabolic capabilities) as well as frequently occurring mutualistic interactions (e.g. mycorrhiza symbiosis) of soil organisms. The high vertical and horizontal diversity of soil food webs maintains and stabilises ecosystem functions. As part of the German Biodiversity Assessment (‘Faktencheck Artenvielfalt’), a group of experts summarized the available knowledge on the state and role of soil biodiversity in Germany. Here, we highlight the role of biodiversity in soils as a driver of ecosystem multifunctionality and buffer against perturbation by human activities, e.g. by mediating the storage and release of greenhouse gases. Through their outstanding contribution to decomposition of dead organic matter, soil organisms control the carbon balance of terrestrial ecosystems, and thus can contribute to climate protection. We further discuss the multifunctionality of soil organisms as a basis for stable ecosystem functioning. Taken together, soil biodiversity, through its emerging properties, is as a key player in processes that govern terrestrial systems, and as such needs to find more consideration in ecosystem sustainability and restoration.